<h3>
Answer:</h3>
- y = -(x -3)² +3 . . . . (agrees with your answer)
- see the attachment for a graph
<h3>
Step-by-step explanation:</h3>
Factoring the leading -1 from the first two terms, we have ...
... y = -(x² -6x) -6
Adding 9 inside parentheses to complete the square, then adding the opposite amount outside parentheses, we have ...
... y = -(x² -6x +9) -6 +9
... y = -(x -3)² +3
Answer:
3in up per foot across
Step-by-step explanation:
4ft across 12in height
6ft across 18in height
So for every 2ft it goes up 6” which is a ratio of 1ft:3in so the answer to the rate of change is 3in up per 1ft across
Answer:
I'm gonna go with D
Step-by-step explanation:
If it's wrong meh bad
Answer:
x = 2, y = -3
Step-by-step explanation:
Add them together and get
9x + 8y - 9x - 9y = -6 + 9
-y = 3
so y = -3.
Sub it into the first equation and get
9x + 8(-3) = -6
9x - 24 = -6
9x = -6 + 24 = 18
x = 18/9 = 2